The Influence Of Consumer Behavior and Product Design On Purchasing Decisions Of Asus Notebooks at PT. Primajaya Multi Technology Medan - Sylvia; Friska, Rina (Journal Boas : Business, Economics, Accounting And Management, 2023)
This study aims to examine the effect of consumer behavior and product design on purchasing decisions of Asus notebooks at PT. Primajaya Multi Technology, Medan. The object of this research is the consumers of PT. Primajaya Multi Technology, Medan. The basis for selecting this sample is the non-probability sampling method using the accidental sampling technique. The data applied in this study are primary data, data obtained from questionnaires distributed to 30 respondents. The analytical method used is multiple linear regression. The percentage of consumer behavior (X1) to purchasing decisions (Y) is 11.9%. This proves that consumer behavior affects the performance of purchasing decisions by 11.9% and the rest is influenced by other factors not examined.The percentage of product design (X2) to purchasing decisions (Y2) is 52.4%. This proves that Product Design affects the performance of purchasing decisions by 52.4% and the rest is influenced by other factors not examined.The percentage of consumer behavior (X1) and product design (X2) on purchasing decisions (Y) is 57%. This proves that Consumer Behavior and Product Design affect the performance of purchasing decisions by 57% and the rest are influenced by other factors not examined.